Histological Examination of Horse Chestnut Infection by Pseudomonas syringae pv. aesculi and Non-Destructive Heat Treatment to Stop Disease Progression - de Keijzer, Jeroen; van den Broek, Lambertus A. M.; Ketelaar, Tijs; van Lammeren, André A. M. (PLOS ONE, 2012)
Since its emergence in Northwest Europe as a pathogen that infects trunks and branches of Aesculus spp. (the horse chestnuts) approximately one decade ago, Pseudomonas syringae pv. aesculi has rapidly established itself as major threat to these trees. Infected trees exhibit extensive necrosis of phloem and cambium, which can ultimately lead to dieback. The events after host entry leading to extensive necrosis are not well documented. In this work, the histopathology of this interaction is investigated and heat-treatment is explored as method to eradicate bacteria associated with established infections. The early wound-repair responses of A. hippocastanum, both in absence and presence of P. s. pv. aesculi, included cell wall lignification by a distinct layer of phloem and cortex parenchyma cells. The same cells also deposited suberin lamellae later on, suggesting this layer functions in compartmentalizing healthy from disrupted tissues. However, monitoring bacterial ingress, its construction appeared inadequate to constrain pathogen spread. Microscopic evaluation of bacterial dispersal in situ using immunolabelling and GFP-tagging of P. s. pv. aesculi, revealed two discriminative types of bacterial colonization. The forefront of lesions was found to contain densely packed bacteria, while necrotic areas housed bacterial aggregates with scattered individuals embedded in an extracellular matrix of bacterial origin containing alginate. The endophytic localization and ability of P. s. pv aesculi to create a protective matrix render it poorly accessible for control agents. To circumvent this, a method based on selective bacterial lethality at 39°C was conceived and successfully tested on A. hippocastanum saplings, providing proof of concept for controlling this disease by heat-treatment. This may be applicable for curing other tree cankers, caused by related phytopathogens.